Synopsis on the Linkage of Alzheimer's and Parkinson's Disease with Chronic Diseases. (15th November 2014) - Jabir, Nasimudeen R.; Firoz, Chelapram K.; Baeesa, Saleh S.; Ashraf, Ghulam Md; Akhtar, Suhail; Kamal, Warda; Kamal, Mohammad A.; Tabrez, Shams
Summary Neurodegeneration is the progressive loss of neuronal structure and function, which ultimately leads to neurological disorders such as Alzheimer's disease (AD), Parkinson's disease (PD), multiple sclerosis, and Huntington's disease. Even after the recent significant advances in neurobiology, the above‐mentioned disorders continue to haunt the global population. Several studies have suggested the role of specific environmental and genetic risk factors associated with these disorders. However, the exact mechanism associated with the progression of these disorders still needs to be elucidated. In the recent years, sophisticated research has revealed interesting association of prominent neurodegenerative disorders such as AD and PD with chronic diseases such as cancer, diabetes, and cardiovascular diseases. Several common molecular mechanisms such as generation of free radicals, oxidative DNA damage, aberrations in mitochondrial DNA, and dysregulation of apoptosis have been highlighted as possible points of connection. The present review summarizes the possible mechanism of coexistence of AD and PD with other chronic diseases.